Techno-economic Comparison of Timer and Optimal Switching Control applied to Hybrid Solar Electric Water Heaters - Hohne, P.A.; Kusakana, K.; Numbi, B. P. (Proceedings of the ... Conference on the Industrial and Commercial Use of Energy (Print), 2018)
In this paper, an optimal energy control model is used to evaluate the potential energy cost saving of a hybrid solar water heater. The aim is to maximize energy cost savings under time-based pricing while maintaining the desired water temperature of the hot water user. The optimally controlled system is compared to traditional timer based controlled system with the same layout as the proposed system. The hybrid water heating system is modelled and simulated using Matlab. From the formulated objective function and the case study in this work, the results present that using an optimally controlled hybrid heater will have an approximate annual cost saving of 20.8%.